Pengaruh Profitabilitas, Likuiditas dan Kebijakan Dividen terhadap Nilai Perusahaan dengan Komite Audit sebagai Pemoderasi - Ni Kadek Handayani; I Gede Cahyadi Putra; Ida Ayu Ratih Manuari (Jurnal Inovasi Akuntansi (JIA), 2023)
The level of company competition in Indonesia is increasing, every company is expected to be able to improve and be able to maintain its current business advantage. Companies such as manufacturing, services and trade compete to be the best so that it spurs companies to make various inventions and business tactics to avoid losses. This study aims to examine and analyze the effect of profitability, liquidity, dividend policy on firm value with the audit committee as a moderating variable in manufacturing companies listed on the Indonesian stock exchange in 2019 - 2021. This research was conducted on Manufacturing Companies listed on the Indonesia Stock Exchange. The population used in this study were all Manufacturing Companies listed on the Indonesia Stock Exchange. The sample of this research were 53 companies with 3 years of observation so that 159 research samples were obtained using purposive sampling method. Source of data in this research is secondary data. The data analysis technique used in this study is the Moderated Regression Analysis (MRA) technique. The results of the analysis show that Profitability has a positive effect on firm value. Liquidity has no effect on firm value. Dividend policy has a positive effect on firm value. The audit committee has a positive effect on firm value. The audit committee is able to moderate the relationship between profitability and firm value. The audit committee is unable to moderate the relationship between liquidity and firm value, but the audit committee is able to moderate the effect of dividend policy on firm value.